Soil assessment after chemical accidents using metabolic profiling and microbial community evaluation - Kim, Naeun; Ahn, Yongtae; Jo, Jungman; Pyo, Heesoo; Lee, Jeongae; Choi, Jaeyoung (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
This study investigated the effects of accidental contamination of soils with phenol, toluene, nitric acid, and hydrogen fluoride (HF) by simulating chemical leakage in the soil with/without rain and characterizing the resulting metabolites and microbial. In the case of acid leakage, pH and cation exchange capacity were decreased, and the content of fluoride ion was increased in case of HF leakage. Using mass spectrometry-based metabolomics analysis, phytosphingosine was detected as a distinguishing metabolite in soils contaminated with phenol and HF in rain conditions. Microbial communities were identified by 16s rRNA metagenome sequencing. Sphingomonas was one of the dominant species in soils contaminated with phenol and HF. These results suggest that phytosphingosine and Sphingomonas might be used as biomarkers to evaluate the status of soils contaminated with phenol or HF. Under simulated rain conditions, the species alpha-diversity index of soil microbes and the physicochemical properties of the soil indicated values close to those of the uncontaminated soil. Rain played an important role in the recovery of microbial and metabolic profiles after chemical accidents. Metabolic profiling and microbial community analysis can serve as a diagnostic tool for ecotoxicological research at chemical accident sites. (C) 2020 Elsevier Ltd. All rights reserved.